COMMUNITY ENGAGEMENT, SERVICE LEARNING AND STUDENT SOCIAL RESPONSIBILITY: IMPLICATIONS FOR SOCIAL WORK EDUCATION AT SOUTH AFRICAN UNIVERSITIES: A CASE STUDY OF THE UNIVERSITY OF FORT HARE - Maistry, Margie (Social Work/Maatskaplike Werk, 2012)
In aspiring towards promoting a developmental state after 1994, the democratic government of South Africa framed its social policies within a developmental paradigm, which underpins its attempt to transform the public sector. Higher education institutions (HEIs) are considered a critical part of the post-apartheid transformation agenda, given that most universities in South Africa were created in line with the oppressive regime of apartheid. They lacked legitimacy and a natural reciprocal relationship with the broader social, cultural and economic environment (Mamphiswana & Noyoo, 2002).